ECONOMIC LAW AND CONFLICT: ELEMENTS OF CRITICISM OF THE LEGAL FORM - Possas, Thiago Lemos [UNESP] (Revista da Faculdade de Direito da UFMG, 2022)
The article deals, fundamentally, with Economic Law and the criticism it made possible to the contemporary legal phenomenon. A discussion addresses a central issue of “conflict”, encompassed by social constitutions, or a data given by the theory of the right to decide such conflicts, as well as the configuration of the current legal phenomenon and the possibilities of breaking the “reification” with the aid from Economic Law. Therefore, consider Economic Law as adjusting the right of access to individual social rights, contrary to the claim of the legal history of everything that encompasses, “colonizing” sociability in its entirety, figuring as a method of analyzing the law, based on the understanding of law, as an integral part of social reality. Economic Law arises from the “crisis” and serves to try to identify and deal with situations of conflict, since it indicates social clashes and seeks to resolve them, but also seeks to display them as options open to social ones. Economic law must go beyond the decision and identify the conflicts to be disputed by progressive social forces. With that, it works as a tool to be used against reification (Lukács) of the legal phenomenon. For such an undertaking, it is imperative to approach other branches of knowledge, such as a political theory, a theory of law and a theory of the state. An interdisciplinary approach is essential for Economic Law to be able to fulfill its vocation.
DIREITO ECONÔMICO E CONFLITO: ELEMENTOS DE CRÍ-TICA DA FORMA JURÍDICA
Keywords: Conflict decidability; Economic Law; Reification